Analysis of Perceived Factors Affecting Tourist Satisfaction in Mountain Tourism: A Study in Mount Papandayan, Indonesia - Vindiana, Afina Putri; Novani, Santi; Mayangsari, Lidia; Alamanda, Dini Turipanam (E-Journal of Tourism; Volume 7 Number 1 (March 2020)DO - 10.24922/eot.v7i1.55878, 2020)
Although the mountain is a popular tourist destination, research regarding mountain tourism is still limited. Over the years, researches on tourist satisfaction covered a more general context of tourism, without specifically analyzing mountain tourism. Therefore, this research aims to investigates factors influencing tourists’ satisfaction on mountain tourism, with Mount Papandayan, Garut Regency, West Java, Indonesia, as a case. Eleven variables regarding tourist satisfaction were derived from several interviews with Mount Papandayan’s management staff and 30 tourists that were hiking and camping on Mount Papandayan. A sample of 100 respondents, who were the Mount Papandayan’s tourists that had been hiking and camping, completed questionnaires. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) was used to analyze the data. The results show that there are three factors that affect tourist’s satisfaction in mountain tourism, which are ‘infrastructure and facilities’, ‘natural resources’, and ‘mountain area’s atmosphere’, while CFA validated the model fit. The results also indicated a significant relationship between the three factors. This research provides an opportunity for broader research opportunities in mountain tourism, especially in tropical countries. Keywords : mountain tourism, satisfaction, EFA, CFA